Impact of type of graft material on outcome of tympanoplasty: a comparison between temporalis fascia and cartilage with perichondrium - Tadke, Kanchan; Ghorpade, Randhir; Lahane, Vaibhav; Mundada, P. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Various graft materials have been used to repair tympanic membrane perforations. Temporalis fascia and cartilage with or without perichondrium are the most commonly used materials. The objective of the study was to compare the anatomical and functional success in type I tympanoplasty by using cartilage- perichondrium graft with that of temporalis fascia in a homogenous group of population. Methods: 64 patients with chronic otitis media - mucosal type were included in the study. This prospective, randomized controlled trial was conducted at a tertiary care centre between December 2012 to October 2014. Patients were grouped randomly between temporalis fascia (34/64) and cartilage group (30/64). In the fascia group, the graft was placed by underlay technique. In the cartilage group, tragal cartilage was thinned by cartilage thinner keeping the perichondrium attached on one side. The graft was placed by underlay or over-underlay technique. Postoperative results i.e. graft take up (anatomical success) and hearing improvement (functional success) were evaluated at 6 months. Results: Graft take up rate was 94.11% for fascia group and 96.66% for cartilage group. The mean pure tone air bone gaps pre and postoperatively in the fascia group were 26.4±6.55 dB and 11.47±6.5 dB respectively, whereas for cartilage-perichondrium group, the values were 28.3±5.86 dB and 13.2±6.48 dB respectively. There was no statistically significant difference in the graft take up rate and postoperative hearing improvement between the two groups (p≥0.05). Conclusions: Cartilage with perichondrium can be considered as an alternative to more traditional grafting material for tympanic membrane reconstruction.